Dopant-free polymeric hole transport materials for efficient CsPbI2Br perovskite cells with a fill factor exceeding 84%. Issue 25 (3rd June 2020) - Wang, Pang; Wang, Hui; Jeong, Mingyu; Lee, Sang Myeon; Du, Baocai; Mao, Yuchao; Ye, Fanghao; Zhang, Huijun; Li, Donghui; Liu, Dan; Yang, Changduk; Wang, Tao
Abstract : p-Type semiconductor PBDB-T and its derivatives have been explored as dopant-free hole transport materials for CsPbI2 Br inorganic perovskite solar cells, with PBDB-T-Si enabling a PCE of 15.6% and FF exceeding 84%. Abstract : Inorganic perovskite solar cells (PSCs) have attracted extensive attention in recent years due to their excellent thermal stability. The CsPbI2 Br PSCs, combining the merits of stable CsPbBr3 and efficient CsPbI3, demonstrate tremendous application potential. In this work, n–i–p structured inorganic CsPbI2 Br PSCs are fabricated using ZnO as the electron transport material (ETM) and dopant-free PBDB-T and its derivatives as the hole transport materials (HTMs). Alkylsilyl-substituted PBDB-T ( i.e. PBDB-T-Si ) based devices demonstrate the best efficiency of 15.60% (compared to 14.20% of the PBDB-T based reference device) with an ultrahigh fill factor over 84% due to the deep highest occupied molecular orbital energy levels, superior hole mobility and quasi-ohmic contact characteristics. However, fluorine- and chlorine-substituted PBDB-T ( i.e. PBDB-T-2F and PBDB-T-2Cl ) based devices exhibit enhanced open circuit voltages but decreased short circuit current densities due to the unbalanced hole extraction and large leakage current at the interface, giving moderate efficiencies of 14.87 and 14.03%, respectively. Our work provides a sophisticated analysis of various optoelectronic properties of polymeric HTMs and points out that the quasi-ohmic/ohmic contact plays a critical role in determining device performance.